دور المحاسبة الاستراتيجية في دعم الميزة التنافسية بالمنشآت الصناعية: دراسة على عينة من المصانع السودانية - أبكر، محمد إسحق عبدالله; عثمان، محي الدين محمد إبراهيم (جامعة بورسعيد - كلية التجارة, 2019)
The goals of this study is trying to acknowledge the strategic accounting in supporting the competitive advantage of the Sudanese industrial construction through connecting the strategic accounting with the dimension of competition representing in low cost, quality, response for the customer and innovation. This study depends on the inductive, deductive, descriptive and analytical methods. To verify the goals of this study, there were 60 questionnaires, which were used in a sample of Sudanese industrial factories represented in Mega Company for industrial food limited. This study resulted in promoting the strategic accounting to competitive advantage in the industrial construction through the existence of relation between the strategic accounting and the dimension of competitive advantage represented in low cost, quality, and responses for customer and innovation. This study recommended to the necessity of the importance of strategic accountancy in the industrial construction because it rises for the competitors price for production pricing, also due to the financial structure to industrial construction through cash-follow for its production. The necessity for the industrial construction by decreasing the cost for its high quality and responds for its customer requirements, innovation, creation for new ideas to promote its competitive advantage in production.
هدفت هذه الدراسة إلى معرفة دور المحاسبة الاستراتيجية في دعم الميزة التنافسية بالمنشآت الصناعية السودانية، وذلك من خلال ربط المحاسبة الاستراتيجية بأبعاد الميزة التنافسية المتمثلة في التكلفة المنخفضة، الجودة، الاستجابة للعميل والإبداع. وقد اعتمدت الدراسة على المنهج الاستنباطي والاستقرائي والوصفي التحليلي. ولتحقيق هدف الدراسة وزعت (60) استبانة لعينة من المنشآت الصناعية بالسودان المتمثلة في شركة ميقا للصناعات الغذائية المحدودة. خلصت الدراسة أن المحاسبة الاستراتيجية تدعم الميزة التنافسية بالمنشآت الصناعية وذلك من خلال وجود علاقة ارتباط بين المحاسبة الاستراتيجية وأبعاد الميزة التنافسية المتمثلة في التكلفة المنخفضة، الجودة، الاستجابة للعميل والإبداع. أوصت الدراسة بضرورة الاهتمام بالمحاسبة الاستراتيجية في المنشآت الصناعية لأنها تهتم بأسعار المنافسين عند تسعير المنتجات، وكذلك الاهتمام بالهيكل المالي للمنشأة الصناعية من خلال التدفق النقدي لمنتجاتها. وضرورة اهتمام المنشأة الصناعية بتخفيض تكلفة منتجاتها، وأن تنتج منتجات ذات جودة عالية، وتستجيب لمتطلبات عملائها، وأن تبدع وتبتكر أفكار جديده لتدعم ميزتها التنافسية.
Keywords: المحاسبة الاستراتيجية -- الميزة التنافسية -- المنشآت الصناعية -- المصانع السودانية